Bacterial expression and isotope labeling of AIMP1/p43 codosome protein for structural studies by multidimensional NMR spectroscopy - Vorobyova, N.V.; Lozhko, D.N.; Zhukov, I.Yu.; Kornelyuk, A.I. (Вiopolymers and Cell, 2015)
AIMP1/p43 protein is a structural component of multisynthetase complex (codosome) in eukaryotes, which reveals both tRNA binding and cytokine activities. Aim. Bacterial expression and purification of isotopically-labeled recombinant AIMP1/p43 protein in E. coli cells for studying its solution structure by multidimensional NMR spectroscopy. Methods. AIMP1/p43 protein was expressed in E. coli BL21(DE3)pLysE cells on M9 minimal medium with 15N isotope labeling and purified by metal-chelated chromatography. Heteronuclear 2D 1H-15N NMR experiments were performed in solution at 293 K on Agilent DDR2 800 NMR spectrometer. Results. The AIMP1/p43 protein was obtained in uniformly 15N-labeled form as an NMR sample. A high dispersion of resonance signals in the 2D 1H-15N HSQC NMR spectra confirmed the presence of its compact 3D protein structure. The NMR spectrum of AIMP1/p43 demonstrated a high signal-to-noise ratio and sufficient stability to acquire other multidimensional NMR data sets for determination of the structure of AIMP1/p43 protein in solution. Conclusions. The 15N-labeled AIMP1/p43 protein was stable for 4–7 days, which makes possible acquiring the critical NMR experimental data for detailed structural analysis in solution. Our data on the initial NMR spectra indicated the presence of some additional signals in comparison with the NMR spectrum of EMAP II which could be assigned to amino acids of the N-terminal α-helical fragment of AIMP1/p43. AIMP1/p43 – структурний компонент мультисинтетазного комплексу (кодосома) евкаріот, проявляє тРНК зв’язуючу та цитокінову активність. Мета. Провести бактеріальну експресію та очистку ізотопно-міченого рекомбінантнога білка AIMP1/p43 в клітинах E. coli для вивчення його просторової структури методами мультивимірної ЯМР спектроскопії. Методи. AIMP1/p43 був експресованний в клітинах E. coli BL21 (DE3) pLysE на мінімальному середовищі М9 з міченням ізотопом 15N та очищено за допомогою метал-хелатуючої хроматографії. Гетероядерні двомірні 1H-15N ЯМР експерименти проводилися в розчині при температурі 293 К на ЯМР спектрометрі Agilent DDR2 800. Результати. Білок AIMP1/p43 був отриманий в 15N-міченій формі в якості ЯМР зразка. Висока дисперсія сигналів у двомірниї ЯМР спектрах 1H-15N HSQC підтверджує наявність компактної тривимірної структури білка. ЯМР спектр AIMP1/р43 виявляє значне співвідношення сигнал-шум та достатню стабільність, щоб застосувати інші багатовимірні ЯМР експерименти, для визначення структури AIMP1/p43 білка у розчині. Висновки. 15N-мічений білок AIMP1/p43 зберігає стабільність протягом 4–7 днів, що дає можливість подальшого отримання важливих ЯМР експериментів для проведення детального структурного аналізу білка у розчині. Наші дані первинного аналізу даних ЯМР вказують на присутність деяких додаткових сигналів у порівнянні зі спектрами ЯМР EMAP II, які можуть бути віднесені до амінокислот N-кінцевий α-спірального фрагмента AIMP1/р43. Белок AIMP1/p43 является структурным компонентом мультисинтетазного комплекса (кодосома) эукариот, проявляет тРНК связующую и цитокиновую активность. Цель. Провести бактериальную экспрессию и очистку изотопно-меченого рекомбинантного белка AIMP1/p43 в клетках E. coli, для изучения его пространственной структуры методами мультимерной ЯМР спектроскопии. Методы. AIMP1/p43 экспрессировали в клетках E. coli BL21 (DE3) pLysE на минимальной среде М9 с мечением изотопом 15N и очистили с помощью металл-хелатирующий хроматографии. Гетероядерные двухмерные 1H-15N ЯМР эксперименты проводились в растворе при температуре 293 К на ЯМР спектрометре Agilent DDR2 800. Результаты. Белок AIMP1/p43 был получен в 15N-меченой форме в качестве ЯМР образца. Высокая дисперсия сигналов в двумерных ЯМР спектрах 1H-15N HSQC подтверждает наличие компактной трехмерной структуры белка. ЯМР спектр AIMP1/р43 показывает значительное соотношение сигнал-шум и достаточную стабильность, чтобы применить другие многомерные ЯМР эксперименты для определения структуры AIMP1/p43 белка в растворе. Выводы. 15N-меченый белок AIMP1/p43 сохраняет стабильность в течение 4–7 дней, что дает возможность дальнейшего получения важных ЯМР экспериментов для проведения детального структурного анализа белка в растворе. Наши данные первичного анализа данных ЯМР указывают на присутствие некоторых дополнительных сигналов в сравнении со спектрами ЯМР EMAP II, которые могут быть отнесены к аминокислот N-концевой ?-спирального фрагмента AIMP1/р43.